Trends and Trajectories in the Software Industry: implications for the future of work - Laato Samuli; Mäntymäki Matti; Islam AKM Najmul; Hyrynsalmi Sami; Birkstedt Teemu (SPRINGER, 2022)
In this study, we explore prominent contemporary technology trajectories in the software industry and how they are expected to influence the work in the software industry. Consequently, we build on cultural lag theory to analyze how technological changes affect work in software development. We present the results from a series of expert interviews that were analyzed using the Gioia method. Moreover, we identify a set of technology trends pertinent to software development from which we derive four main changes affecting the future of work in software development: (1) a shift toward scalable solutions, (2) increased emphasis on data, (3) convergence of IT and non-IT industries, and (4) the cloud as the dominant computing paradigm. Accordingly, this study contains insights into how technology (as an element of material culture) influences non-material culture, as exemplified by the work involved in software development.